Is It All about the Higher Dose? Why Psychoanalytic Therapy Is an Effective Treatment for Major Depression. (4th September 2014) - Zimmermann, Johannes; Löffler‐Stastka, Henriette; Huber, Dorothea; Klug, Günther; Alhabbo, Sarah; Bock, Astrid; Benecke, Cord
Abstract : Empirical evidence for the effectiveness of long‐term psychodynamic psychotherapy (LTPP) in patients with mood disorders is growing. However, it is unclear whether the effectiveness of LTPP is due to distinctive features of psychodynamic/psychoanalytic techniques or to a higher number of sessions. We tested these rival hypotheses in a quasi‐experimental study comparing psychoanalytic therapy (i.e., high‐dose LTPP) with psychodynamic therapy (i.e., low‐dose LTPP) and cognitive–behavioural therapy (CBT) for depression. Analyses were based on a subsample of 77 subjects, with 27 receiving psychoanalytic therapy, 26 receiving psychodynamic therapy and 24 receiving CBT. Depressive symptoms, interpersonal problems and introject affiliation were assessed prior to treatment, after treatment and at the 1‐, 2‐ and 3‐year follow‐ups. Psychoanalytic techniques were assessed from three audiotaped middle sessions per treatment using the Psychotherapy Process Q‐Set. Subjects receiving psychoanalytic therapy reported having fewer interpersonal problems, treated themselves in a more affiliative way directly after treatment and tended to improve in depressive symptoms and interpersonal problems during follow‐up as compared with patients receiving psychodynamic therapy and/or CBT. Multilevel mediation analyses suggested that post‐treatment differences in interpersonal problems and introject affiliation were mediated by the higher number of sessions, and follow‐up differences in depressive symptoms were mediated by the more pronounced application of psychoanalytic techniques. We also found some evidence for indirect treatment effects via psychoanalytic techniques on changes in introject affiliation during follow‐up. These results provide support for the prediction that both a high dose and the application of psychoanalytic techniques facilitate therapeutic change in patients with major depression. Copyright © 2014 John Wiley & Sons, Ltd. Key Practitioner Message: Psychoanalytic therapy is an effective treatment for major depression, especially in the long run. The differential effectiveness of psychoanalytic therapy cannot be fully explained by its higher dose. Distinctive features of psychoanalytic technique (e.g., focusing on patients' dreams, fantasies, sexual experiences or childhood memories) may play an important role in establishing sustained therapeutic change.